Perancangan Sistem Informasi Pemesanan Paket Dokuemntasi Wedding Berbasis Web Menggunakan Metode Prototype : Studi Kasus : Light Scape Visual - Bimantara Ramadhan; Agus Suharto (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
Wedding Documentation is a service that helps every couple who will capture their wedding moments with photos and videos. Light Scape Visual is a wedding photography service located in the South Tangerang city area. Light Scape Visual is a place that provides several types of services according to the wishes of customers in the field of photography and videography. The ordering information system makes Light Scape Visual a wedding documentation service by utilizing web-based information technology, with the aim of expanding the area of promotion and sales of wedding packages and simplifying the ordering process. In making the ordering of this wedding documentation web information system using PHP programming with the Laravel and MySQL frameworks. This wedding documentation ordering information system is very helpful for those who don't want to be bothered with their wedding documentation problems and provides convenience for ordering packages that operate online.